A nutritional quality audit for food retailers - Hairsnape, Simon Phillip (Cranfield University, 1990)
There is increasing evidence that our diet is implicated in several common diseases including coronary heart disease, the single largest cause of death in Britain. The development and implementation of nutrition policies is seen as a way of modifying the diet of individuals and communities with the aim of reducing the prevalence of disease. To-date policy implementation has concentrated on health education aimed at the individual. The thesis suggests that this strategy has limited effectiveness and that health workers need to consider new strategies concerned with food availability. The thesis proposes that the food retail sector is the 'gate keeper' of the nation's food supply and that, po te ntially it could do much to promote individual and community nutrition. After analysing the various issues involved the thesis suggests that retailers are not doing as much as they could be, and what they are doing might be ineffective. It is further suggested that a major obstacle to produ ci ng strategies aimed at retailers is that no method exists for quantifying their contributions. It is proposed that a n e w research instrument is needed to enable health workers to develop such strategies and monitor their implementation. This research instrument would allow workers to undertake an objective, reliable and quantifiable method of analysing those areas that retailers are and are not using to promote nutrition. The thesis hypothesises that the ability to measure contributions might stimulate the retailer's competitive nature to do more. The thesis therefore proposes and pilots a nutritional quality audit for food retailers. The audit is not a standard research instrument and therefore requires the development of new concepts and methods for its design. The thesis concludes by suggesting how this new instrument might be further developed and used to encourage food retailers to realise their potential for promoting individual and community nutrition.